Gender consciousness and privilege - Brody, Celeste M. (Falmer Press, 2000)
Develops a new framework for working in schools that helps educators make informed decisions about change at individual, classroom, curricular and school levels on behalf of gender equity. Addresses the issue of understanding the impact of education on the two sexes, and looks at responsibility for creating gender-fair environments, organising work and creating environments for learning. The book draws on a two-year study into the role that gender played as three Catholic high schools prepared to move from single sex to coeducation. It does not weigh the advantages of single sex against coeduc.